PENGEMBANGAN SISTEM INFORMASI ADMINISTRASI KEPENDUDUKAN BERBASIS LAN PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KOTA SURAKARTA - Arkha Cristya Primadana; Dwi Retnoningsih; Firdhaus Hari Saputro (Universitas Sahid Surakarta, 2013)
Civic Administration Information System (SIAK) made by the writer when he had apprenticeship is run well. By the time being, the SIAK users find some problems,because the SIAK being used now has some deficiencies, those are: it is stand alone, unspecific civic data, not optimal form interface, uncomplete KTP data, and uncertaindata redundancy. It based Local Area Network (LAN) is a multiuser information system used to process computerized civils data and is able to minimalize data redundancy.The output of SIAK is family Certificate (KK), Indonesian Biodata, Identity Data Card (KTP), and Migration Certificate.